MARKETING STRATEGY TO INCREASE SALES DURING THE COVID-19 PANDEMIC - Indria Yuli Susanti (STIE Mandala Jember, 2022)
The COVID-19 pandemic which has impacted all sectors has caused people's purchasing powerto decline. This has an impact on the decline in sales of itinerant vegetable seller in KarangrejoVillage, Sumbersari District, Jember Regency. They do various marketing strategies in an effortto increase sales. This study aims to obtain an overview of the marketing strategies carried out byitinerant vegetable seller to increase sales during the COVID-19 pandemic, and how effectivetheir strategies are in increasing sales. This research is a descriptive qualitative research, and thedata collection technique used is observation and open interviews with itinerant vegetable seller.The result of this research is that itinerant vegetable seller use the marketing mix, namelyproduct, price, place, and promotion as a marketing strategy to increase sales. The fourmarketing mixes are effective in increasing sales by 70% to 80%. And of the four marketingmixes, product is the most effective marketing mix type in increasing sales.Keywords: Sales Strategy, Sales, COVID-19 Pandemic